Building the Customers Loyalty of Hennes and Mauritz Brand Fashion in Indonesia Using Twitter - Augustine, Liesta; Rewindinar, Rewindinar; Marta, Rustono Farady (International Journal of Social Science and Business, 2021)
Economic growth has accelerated in recent years. Company owners’ tactic was to used social media as a bridge to reach out to customers. A brand gains who gains consumers would attempt to establish a relationship with them and also gain their commitment. This is referred to as consumer loyalty. This loyalty was very critical to the brand’s long term sustainability and growth. Customers’ satisfaction can be used to gain customer loyalty. The aim of this study was to examine H&M's use of Twitter as a social networking platform for building consumer loyalty. The study was carried out using the netnography approach, in which data was gathered by observation on Twitter. The netnography approach is an ethnographic method that combines the use of internet with ethnography. The findings in this research conclude that games and interaction will undoubtedly be required to capture customers' interest and generate their loyalty.